2022
DOI: 10.1007/s00122-022-04064-5
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping-by-sequencing and genome-wide association study reveal genetic diversity and loci controlling agronomic traits in triticale

Abstract: Key message The genetic diversity and loci underlying agronomic traits were analysed by the reads coverage and genome-wide association study based genotyping-by-sequencing in a diverse population consisting of 199 accessions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…GBS coverage analysis represents a convenient and fast method for analyzing the genome composition of allopolyploids 32 , 33 . We found that the presence of parental incompatible alleles triggers major rearrangements in wheat and rye chromosomes in wheat-rye hybrids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GBS coverage analysis represents a convenient and fast method for analyzing the genome composition of allopolyploids 32 , 33 . We found that the presence of parental incompatible alleles triggers major rearrangements in wheat and rye chromosomes in wheat-rye hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of rye chromosomes was compensated by an extra pair of 2D or A-genome chromosomes (possibly 2A) in plants with 2n = 56. The authors suggested that the loss of 2R and 5RS with their replacement by chromosomes of the D and A genome contributes to the improvement of octoploid triticale 33 , 53 . The vast changes in spike architecture caused by nullisomy of the 2R and 5R chromosomes of rye were found in androgenic offspring of hexaploid triticale (× Triticosecale Wittmack).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of a high-quality triticale reference genome, wheat and rye reference genomes are useful resources for the identification of candidate genes that underlie markers associated with IVD traits in triticale [ 8 ]. Based on MTAs, candidate genes were identified which were of particular relevance for variation in IVD because they are putatively involved in plasma membrane transport, cytoskeleton organisation, enzyme activity, carbohydrate metabolic processes, protein phosphorylation, and sterol biogenesis (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hexaploid triticale contains wheat and rye genomes, and shows relatively superior vigor and reproductive stability ( Lukaszewski and Gustafson, 1987 ; Cheng and Murata, 2002 ). Studies on genome-wide diversity have revealed diversified genetic structures in rye and Triticale germplasm ( Bolibok-Bragoszewska et al., 2014 ; Sun et al., 2022 ; Cao et al., 2022 ). Among the rye chromosomes, the S. cereale chromosome 6R has displayed rapid structural change and high levels of heterogeneity of heterochromatin blocks, which has been revealed by FISH using tandem repeat probes on different rye cultivars ( Guo et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%